Clinical response at Day 3 of therapy and economic outcomes in hospitalized patients with acute bacterial skin and skin structure infection (ABSSSI). (July 2013) - Amara, Shilpa; Adamson, Robert T.; Lew, Indu; Huang, Xingyue
Abstract Objective: The FDA recently issued guidance for the types of infections that should be included in trials to support an indication for antibacterial treatment. The latest FDA guidance recommends assessing response to drug therapy at 48 to 72 hours as the primary endpoint in clinical trials. This study evaluated clinical and economic outcomes among acute bacterial skin and skin structure infections (ABSSSI) patients hospitalized at a 3000-bed healthcare system in New Jersey. Research design and methods: In this retrospective cohort analysis, adult ABSSSI patients hospitalized between July 2010 and December 2011 were stratified based on infection type: cellulitis/erysipelas and major cutaneous abscess, wound infection, and all ABSSSI. Initial antibiotic therapy was assessed by individual agent, regimen, and MRSA coverage. Day 3 response to initial antibiotic therapy was evaluated based on temperature and lesion cessation outcomes; clinical response rates were assessed by initial therapy and pathogen for each cohort. The impact of response on length of stay (LOS), cost of care, and antibiotic treatment duration were also evaluated. Results: Commonly used antibiotics included vancomycin, cefazolin, piperacillin–tazobactam, and ampicillin–sulbactam; over 40% of patients received empiric therapy with activity against MRSA. Clinical non-response to initial antimicrobial therapy at Day 3 was 39.9%, 30.3%, and 60.7%, for all ABSSSI, cellulitis/abscess, and wound infection patients, respectively. The cost of care among non-responders was over 1.5 times that of responders (p < 0.0001). Non-response to initial therapy was associated with a 3.7 day increase in duration of antibiotic treatment (p < 0.0001). Conclusions: Results of this study demonstrate that a significant percentage of ABSSSI patients, particularly those with wound infection, were not achieving clinical response at Day 3 of therapy. Failure to respond to drug therapy is associated with substantial increases in LOS, antibiotic treatment duration, and cost of care. Limitations: This had the inherent limitations associated with a retrospective chart review; because data was initially collected for clinical rather than research purposes, certain information may have been absent, incomplete, or missed by data abstractors.